Velocity Conference Santa Clara 2015 complete video compilation - O'Reilly, Tim (O'Reilly Media, 2015)
"How fast is fast enough? When it comes to making your websites, apps, and services fast, scalable, resilient, and highly available, the goalposts keep moving. The demand for more never ceases. This complete video compilation of O'Reilly's Velocity 2015 Conference in Santa Clara provides valuable information in several areas to help you keep up. You'll be front-row center for every presentation, whether it's a keynote, a tutorial, or a workshop."--Resource description page.
Title taken from resource description page (Safari, viewed July 1, 2015)
Keywords: Computer software -- Congresses -- Development; Application software -- Congresses -- Development; Logiciels d'application; Développement; Congrès; Application software; Development; Computer software; Development; Conference papers and proceedings